64 Walker Warburg syndrome (WWS) with ISPD genetic mutation- a case report. (30th November 2020) - Muthukumarasamy, Premala; Mansoori, Haroon; Albialy, Ahmed; Tan, Jenn; Brown, Kerry; Henderson, Robert; Callaghan, Bridget; Pincott, Sian; Manzur, Adnan
Abstract : Background: Walker Warburg dystroglycanopathy is the most severe subtype of congenital muscular dystrophies. It is characterised by four consistent features -cobble stone lissencephaly, cerebellar malformation, retinal abnormalities and muscular dystrophy. The incidence is estimated at 1.2 per 100, 000 live births and the life-span in these children is around 3 years. There are more than fifteen causative genes and transmission is autosomal recessive. Case: We describe a boy, born in Kuwait to parents of a consanguineous marriage, premature at 34 weeks gestation with hypotonia, antenatal hydrocephalus and severe eye abnormalities. An MRI brain done at the referring hospital showed cobblestone lissencephaly and severe ventricular dilatation. He was transferred to our centre at corrected age 38 weeks for neurosurgical and medical management. Clinical examination showed central hypotonia with a lack of purposeful movements, macrocephaly from hydrocephalus, left eye buphthalmos and congenital glaucoma, a blind microphthalmic right eye, hearing impairment and bilateral medullary nephrocalcinosis. The creatinine kinase was elevated at 3996U/l. A genetic panel for muscular dystrophy done here detected a homozygous ISPD c.1186G>T p. (Gly396Ter) pathogenic sequence variant, confirming ISPD-related congenital muscular dystrophy. Complications included cerebrospinal fluid leak post ventriculoperitoneal (VP) shunt insertion, recurrent aspiration pneumonia and urinary tract infections.Of note, he developed hypothermia as a side effect from Timolol eye drops as part of his treatment for glaucoma. He underwent a fundoplication gastrostomy ;slowly tolerating feeds with anti-reflux medications, breathing comfortably in air and cooing in response to parents' handling. Within a comprehensive multidisciplinary team effort, lung protective strategies, regular occupational and physiotherapy, he made a good recovery. He was successfully repatriated home with good parental care at corrected age 7 months Conclusion: Prognosis may be poor in WWS, however it is most ethical to provide holistic care, optimise the quality of life and direct genetic counselling.